Macroeconomic Modelling at the Institute: Hopes, Challenges and a Lasting Contribution. (November 2018) - Barrell, Ray; Blake, Andy; Young, Garry
The Institute is a world leader in macroeconomic modelling and forecasting. It has produced quarterly economic forecasts for around sixty years, supported by macroeconomic models. The aim of the original builders of macroeconomic models was to transform understanding of how economies worked and use that knowledge to improve economic policy. In the early years, when computers were rare, macroeconomic modelling was a new frontier and Institute economists were among the first to produce a working model of the UK economy. It is remarkable how quickly models were being used to produce forecasts, assess policy and influence the international macroeconomic research agenda. The models built at the Institute were mainstream in the sense that they followed the contents of standard macroeconomic textbooks, developed with the subject, and fitted the facts as they were known at the time. There were continual improvements in understanding as the subject developed in response to new ideas and developments in the global economy. This article celebrates the development of macroeconomic modelling at the Institute and the contribution it has made to public life.